LGBT sexual health. (April 2022) - Hegazi, Aseel; Pakianathan, Mark
Abstract: There is a growing body of evidence that the syndemic health inequalities in the areas of mental health and substance and alcohol use in lesbian, gay, bisexual and transsexual (LGBT) people contribute to poorer sexual health. This is a diverse population where not only individual behavioural factors, but the wider political, legal, economic, institutional and sociocultural factors are also important drivers of health inequalities. Lesbian women have increased susceptibility to bacterial vaginosis, while trans women and gay and bisexual men have greater vulnerability to sexually transmitted infections and HIV compared to cis-gendered heterosexuals. A non-judgemental attitude and cultural competency in communication are essential for clinical assessments. Consideration must be given to non-genital clinical examination and sampling according to sexual history. There are specific vaccination considerations and those at higher risk of HIV infection require information and access to biomedical prevention interventions. Routine assessments of mental health, substance and alcohol use during sexual health consultations create opportunities for interventions that seek to go beyond infection or fertility control to improve overall health and well-being.